Anna Hofman-Uddgren, Pioneer of Stockholm Cinema Culture. Digitized Tools and Resources for Research on Early Cinema History and Film Reception in Sweden - Stigsdotter, Ingrid (Iluminace, 2022)
An early historian of Swedish cinema described the theatre director and performer Anna Hofman-Uddgren as embodying "an entire epoque in Swedish entertainment life and Stockholm film" (Idestam-Almquist 1959). However, although Hofman-Uddgren included moving images in her variety shows in Stockholm from 1898, and became a pioneer filmmaker, directing six films in 1911, research on Hofman-Uddgren's contribution to Stockholm's cinema culture remains scant. This study, inspired by feminist historiographical perspectives on silent cinema (Bruno 1993; Gaines & Vatsal 2011; Stamp 2015; Gaines 2018) and by work on historical film reception (Staiger 1992; 2000; 2005), argues that Hofmann-Uddgren's relative marginalization in Swedish film history should be considered in the light of other examples of "loss and forgetting" in the discourse around women's contribution to early cinema (Stamp 2015). Additional theoretical and methodological insights come from reflections from within the field of digital humanities (Dang 2020; Hoyt 2019; Mandell 2016). The article asks how computer-based approaches to film research and mass digitization of archival collections affect our understanding of Hofman-Uddgren and her place within the local cinema history of Stockholm.
Keywords: film reception; early cinema history; feminist historiography; Stockholm film culture; women pioneers